The performance evaluation of different logical topologies and their respective protocols for wireless sensor networks - Mohammed Alduais, Nayef Abdulwahab (2015)
Wireless sensor networks (WSNs) are at present a standout amongst the most, guaranteeing areas in the field of information and communication technologies (ICT). This new technology has boundless potential for various applications in distinctive regions, including environmental research, medical application, military, transportation, stimulation, emergency administration, security, and smart spaces. However, several constraints of the sensor nodes are the principal obstacles in planning efficient protocols for WSNs. The major challenges of WSNs include energy dissipation; prolong the network lifetime and throughput. This thesis explores logical topologies in WSN. Logical topologies play the most significant role in the overall performance of the network, including its lifetime, routing efficiency, energy dissipation and overheads. A number of logical topologies have been proposed for WSNs including flat topology, cluster-distributed topology, cluster-centralized topology, and chain topology along with their corresponding routing protocols. In addition, the outcome of the study should definitely performed an important of those parameters of concerned. The simulation experiments are done by using NS-2.34 program for the logical topologies considered are cluster–distributed, chain-based, cluster–centralized and flat with the corresponding protocols of LEACH, PEGASIS, LEACH-C and MTE respectively, while MATLAB is used to plot the graphs. The performance metrics studied are the network lifetime, energy dissipation and aggregate data received at the base station. From the results it can be deduced, that the chain topology (PEGASIS) gives a better performance (network lifetime, energy dissipation and throughput at the base station) overall topologies (LEACH, LEACH-C and MTE).